Father Involvement and Psychological Well-Being of Pregnant Women. Issue 6 (November 2015) - Giurgescu, Carmen; Templin, Thomas N.
Abstract: Purpose: This study examined the relationships among father of the baby involvement during pregnancy, depressive symptoms, and psychological well-being in African American women. Study Design and Methods: Using a prospective study design, a sample of 95 pregnant African American women receiving prenatal care at a medical center in Chicago completed the self-report instruments about father of the baby involvement, depressive symptoms, and psychological well-being twice during pregnancy, once at between 15 and 25 weeks and once between 25 and 37 weeks. Results: Eighty percent of women reported that the father of the baby was involved during their pregnancy. Twenty-eight percent of women had clinically relevant depressive symptoms (CES-D scores ≥16) at the first data collection and 25% of women had clinically relevant depressive symptoms at the second data collection. Compared with women who reported no father involvement during pregnancy, women who reported father involvement during pregnancy had lower levels of depressive symptoms and higher levels of psychological well-being. Clinical Implications: Fathers' involvement is important during pregnancy; nurses should encourage fathers to participate at prenatal visits and ask questions, and educate fathers on pregnancy process and procedures during prenatal care. Abstract : Involvement of the father of the baby during pregnancy has been associated with better maternal and infant outcomes. In this study, pregnant women who reported father involvement had lower levels of depressive symptoms and higher levels of psychological wellbeing than women who indicated that the father of the baby was minimally or not involved. Nurses can encourage father involvement at every interaction during the prenatal period and during labor, birth and postpartum.